If the Code needs to change, let's talk about property and leases - Arbulú Mansilla , Carlos Andrés (Revista de Derecho, 2024)
Within the framework of the commemoration of the forty years of the Peruvian Civil Code, this essay analyses the legal institutions of property, acquisitive prescription and leasing contracts to demonstrate the need for a systematic interpretation of the code, evidencing the need for certain reforms and amendments in this body of law, proposing a series of changes in four articles.
Keywords: Civil Patrimonial Law; transfer of property; lease contract; real estate